2017
DOI: 10.3390/rs9030259
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Random Forest and OBIA Classification Scheme for Mapping Smallholder Agriculture at Different Nomenclature Levels Using Multisource Data (Simulated Sentinel-2 Time Series, VHRS and DEM)

Abstract: Sentinel-2 images are expected to improve global crop monitoring even in challenging tropical small agricultural systems that are characterized by high intra-and inter-field spatial variability and where satellite observations are disturbed by the presence of clouds. To overcome these constraints, we analyzed and optimized the performance of a combined Random Forest (RF) classifier/object-based approach and applied it to multisource satellite data to produce land use maps of a smallholder agricultural zone in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(149 citation statements)
references
References 39 publications
(25 reference statements)
3
138
0
1
Order By: Relevance
“…Typically, the approaches that use these two types of information [5], [6], perform data fusion at descriptor level [3]. This type of fusion involves extracting a set of independent features for each data source (time series, VHSR image) and then stacking these features together to feed a traditional supervised learning method (i. e., Random Forest).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the approaches that use these two types of information [5], [6], perform data fusion at descriptor level [3]. This type of fusion involves extracting a set of independent features for each data source (time series, VHSR image) and then stacking these features together to feed a traditional supervised learning method (i. e., Random Forest).…”
Section: Introductionmentioning
confidence: 99%
“…These new missions revisit the same area more frequently (every four or ten days) [23,24]. These data's fine spatial resolution, global coverage and relatively fine temporal resolution make them of great utility for mapping crop distribution [25,26]. In fact, such high spatial resolution time series with multiple bands and possible derivations contribute large volumes of data that present significant challenges for in-season crop mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the performance of a combination of RF approaches with object-based image analysis for crop mapping has garnered much attention [25,41,42]. However, few studies have paid much attention to producing the early seasonal crop type maps for decision-maker management and mapping crop seasonal dynamics based on new "two high resolution" satellite data.…”
Section: Introductionmentioning
confidence: 99%
“…Combining seasonal optical time series at coarse and moderate resolutions, with an annual VHSR image, improves the accuracy of the classification products [104]. Likewise, with increasing availability of combined optical and radar remote sensing data, research capitalizing the complementarity of both information sources should gain considerable momentum [210].…”
Section: Research Perspectivesmentioning
confidence: 99%
“…These methods are maybe the most accurate, but are the least efficient in terms of time and human resources. Consequently, automated classification approaches were developed, including unsupervised classification [101], single or multi-stage supervised classification [102], decision tree [103], and supervised learning models such as Random Forest or Support Vector Machines [104,105]. Furthermore, Li et al [106] showed that the object-based image analysis (OBIA) approach applied to Landsat, which allowed the use of information about the geometry and topology of the fields, was useful for discriminating irrigated fields.…”
Section: Irrigationmentioning
confidence: 99%